Provision of inadequate information on postnatal care and services during antenatal visits in Busega, Northwest Tanzania: a simulated client study - Eveline T. Konje; Itikija E. Msuya; Dismas Matovelo; Namanya Basinda; Deborah Dewey (BMC, 2022)
Abstract Background Most (94%) of global maternal deaths occur in low- and middle-income countries due to preventable causes. Maternal health care remains a key pillar in improving survival. Antenatal care (ANC) guidelines recommend that pregnant women should be provided with information about postnatal care in the third trimester. However, the utilization of postnatal care services is limited in developing countries including Tanzania. The aim of this study was to investigate the practice of health care workers in providing information on postnatal care to pregnant women during antenatal care visits. Methods A cross sectional study was conducted among health care workers from 27 health facilities that offer reproductive and child health services in Busega district Northwest Tanzania. A simulated client approach was utilized to observe quality of practice among health care workers with minimal reporting bias (i.e., the approach allows observing participants at their routine practices without pretending). Selected pregnant women who were trained to be simulated clients from the community within facility catchment area attended antenatal care sessions and observed 81 of 103 health care workers. Data analyses were carried out using STATA 13. Results Only 38.73% (95% CI; 28.18-49.49%) of health care workers were observed discussing subtopics related to postnatal care during the ANC visit. Few health care workers (19.35%), covered all eight subtopics recommended in the ANC guidelines. Postnatal danger signs (33.33%) and exclusive breast feeding (33.33%) were mostly discussed subtopics by health care workers. Being a doctor/nurse/clinical officer is associated by provision of postnatal education compared to medical attendant, aOR = 3.65 (95% CI; 1.21-12.14). Conclusion The provision of postnatal education during ANC visits by health care workers in this district was limited. This situation could contribute to the low utilization of postnatal care services. Health care workers need to be reminded on the importance of delivering postnatal education to pregnant women attending ANC clinic visits. On job training can be used to empower health care workers of different cadres to deliver postnatal health education during ANC visits. These efforts could increase women's utilization of postnatal care and improve outcomes for mothers and newborns.